One Size Doesn’t Fit All: The Deployment of Police Body-Worn Cameras to Specialty Units - Gaub, Janne E. (International criminal justice review, 2020)
Although body-worn cameras (BWCs) have diffused rapidly in law enforcement both in the United States and abroad, questions have emerged regarding the potential utility of BWCs for specialized police units. Given the near-sole focus on patrol during BWC implementation, the role of specialty units in BWC deployment is often overlooked. Further, the advantages, disadvantages, and challenges associated with BWCs may be unique for specialty units compared to patrol, given their differences in mission and operational focus. We explore this issue using qualitative data from 17 focus groups with 72 officers assigned to specialty units in two midsize Western police departments. The findings highlight the importance of carefully considering unit mission when making decisions about BWCs, especially related to policy and procedure.